A Comprehensive Model of Uncertainty Associated with Radical Innovation. (2nd September 2013) - O'Connor, Gina Colarelli; Rice, Mark P.
Abstract : Large established firms typically focus on enhancing their ability to manage their core businesses, with an emphasis on cost reduction, quality improvements, and incremental innovation in existing products and processes. To sustain competitive advantage over the long term, mature firms must in parallel develop radical innovations (RI) as a basis for building and dominating fundamentally new markets. Management practices that are effective in established businesses are often ineffective and even destructive when applied to RI projects because of higher levels of uncertainty inherent in the latter. Understanding the characteristics of RI projects and the nature of the uncertainty that pervades them is critical to developing appropriate managerial practices. This paper reports the results of a longitudinal study of 12 RI projects in 10 large established U.S.‐based firms. A qualitative, prospective design was used to collect and analyze data. Project team leaders, members, and sponsors for each project were interviewed repeatedly over five years. The analysis centers on the dimensions and characteristics of uncertainty that project teams experienced. The analysis of the challenges they confronted is used to construct a multidimensional model of RI uncertainties. The model identifies four categories of uncertainty as key drivers of project management: technical, market, organizational, and resource uncertainty. Each of these four categories is elaborated in the context of radical innovation and further distinguished via two additional dimensions: criticality and latency. These are substantiated through case based data. Implications for management skills, processes, and appropriate tools associated with radical innovation projects are discussed.